PENGARUH EMPLOYER BRANDING TERHADAP MINAT BERTAHAN KARYAWAN DI BATOO FARM ADVENTUR - Ananda Alvin Adam Asrudin; Rita Mardiana (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This study's primary goal is to assess how employer branding affects Batoo Farm Adventure employees' inclinations to stay on the job. 113 pertinent agency employees were surveyed using a questionnaire in order to gather data at random using a quantitative technique. Instrument testing (validity and reliability), traditional assumption tests (normality and heteroscedasticity), basic linear regression analysis, hypothesis testing (t test and F test), and computation of the coefficient of determination using SPSS software 21st edition were all included in the data evaluation stages. Indicators of work culture and environment, leadership style, salary and rewards, and opportunities for career advancement were used to operationalize the aspects of the company's image as an employer (employer branding). With a regression coefficient of 0.684 and a significance level of 0.000 (less than 0.05), the analytical track record demonstrated the positive and substantial impact of employer branding on staff retention commitment. The employer branding variable's coefficient in predicting retention intention is 40%, according to the coefficient of determination (R2) value, which reached 0.400. The remaining 60% is explained by the contribution of external variables not included in this analysis model. The empirical results show that companies will have a higher steady retention rate if they are skilled at presenting an amazing work reputation and high utility value for their personnel. Leaving this condition aside, the management of Batoo Farm Adventure is recommended to maximize their internal branding strategy, particularly with regard to the factors of a comfortable work environment, a reward system, and a career that is undoubtedly in order. to minimize staff churn and preserve the organization's operational stability.